Refractive Lenticule Implantation for Correction of Ametropia: Case Reports and Literature Review - Lazaridis, A.; Messerschmidt-Roth, A.; Sekundo, W.; Schulze, S. (Klinische Monatsblätter für Augenheilkunde, 2017)
The ReLEx® technique allows correction of refractive errors through the creation and extraction of refractive stromal lenticules. Contrary to excimer laser corneal refractive procedures, where the stromal tissue is photoablated, the extracted lenticules obtained with ReLEx® can be preserved. Recent studies and case reports have described autologous re-implantation and allogeneic implantation of refractive lenticules into femtosecond-laser created stromal pockets in order to reverse the refractive outcome of a myopic corneal refractive procedure, correct hyperopia, aphakia, presbyopia and treat keratoconus. The use of stromal lenticules has also been described for therapeutic purposes, with an allogenic lenticule being transplanted under a LASIK flap in order to restore corneal volume and reduce the refractive error in a case of excessive stromal tissue removal after LASIK. This review summarises the results of the latest case reports and studies that describe the implantation of cryopreserved or fresh refractive stromal lenticules and discusses the feasibility, safety and refractive outcomes of the procedure, on the basis of published literature as well as our own experience.
Keywords: ReLEx; refractive lenticule; implantation; ametropia